Hydrothermal assisted morphology designed MoS2 material as alternative cathode catalyst for PEM electrolyser application. (17th August 2016) - Senthil Kumar, S.M.; Selvakumar, K.; Thangamuthu, R.; Karthigai Selvi, A.; Ravichandran, S.; Sozhan, G.; Rajasekar, K.; Navascues, Nuria; Irusta, Silvia
Abstract: In this work, we developed a simple and cost-effective hydrothermal route to regulate the formation of molybdenum disulfide (MoS2 ) in different morphologies, like, nano-sheet, nano-capsule and nano-flake structure by controlling the reaction temperature and sulphur precursor employed. Such a fine tuning of different morphologies yields a leverage to obtain novel shapes with high surface area to employ them as suitable candidates for hydrogen evolution catalysts. Moreover, we report here the first time observation of MoS2 nano-capsule formation via environmentally benign hydrothermal route and characterized them by X-ray diffraction (XRD), nitrogen adsorption and desorption by Brunaer–Emmett–Teller (BET) method, scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and X-ray photo-electron spectroscopy (XPS) techniques. MoS2 nano-capsules exhibits superior activity towards hydrogen evolution reaction (HER) with a low over-potential of 120 mV (RHE), accompanied by large exchange current density and excellent stability in 0.5 M H2 SO4 solution. MoS2 nano-capsule catalyst was coated on solid proton conducting membrane (Nafion) and IrO2 as anode catalyst. The performance of the catalyst was evaluated in MEA mode for 200 h at 2 V without any degradation of electrocatalytic activity. Highlights: Simple and environmentally benign route is demonstrated to prepare MoS2 material in three different morphologies. A fine control over morphology and purity was achieved. Shape dependence in catalytic activity towards HER was observed. High surface area of nano-sphere MoS2 morphology is responsible for superior electro-catalytic activity.